Penerapan Metode Drill dalam Pembelajaran Bahasa Arab (Studi Kasus di MTsN 9 Kediri) - Husain, Naufal; Rifa’i, Ahmad (Al-Wasil, 2025)
This study aims to examine the application of the drill method in teaching Arabic to MTsN 9 Kediri. The drill method, emphasizing repetitive practice, is believed to strengthen memory retention and enhance students' Arabic language skills, particularly in vocabulary (mufrodat), grammar (qawaid), pronunciation, and speaking ability. This research uses a descriptive qualitative approach, with the Arabic language teacher as the subject and the practice of the drill method during the even semester of the 2024/2025 academic year as the object. Interview results show that the drill method effectively improves student participation and retention of Arabic material. Students demonstrated enthusiasm, positive responses, and significant improvement in pronunciation and sentence structure mastery. The results of this study are expected to provide strategic input for teachers in selecting effective Arabic teaching methods at the madrasah level.